Rancang Bangun Sistem Informasi Akademik Di Akademi Keperawatan Adi Husada Surabaya - Muhammad bagir; Antok Supriyanto; Achmad Arrosyidi (Jurnal Sistem Informasi Universitas Dinamika, 2018)
Adi Husada Nursing Academy is an educational institution in the field of nursing that conducts Diploma lecture 3. Adi Husada Academy Surabaya was established in 1983 and located in Kapasari street Surabaya. During this time, academic difficulties in the recapitulation of attendance of students and lecturers as well as the academic value of the students. This is because the recapitulation is done one by one from the report of 183 lectures. While the recapitulation of academic value of students should be done by selecting one by one with the name of the students with the subject followed. From the existing problems of administrative applications required courses that can assist in the process of recapitulation of attendance of students and lecturers as well as the academic value of students. Recapitulation of student attendance is used to know the status of students in the examination. Based on the results of trials that have been done, the application successfully assist in the process of recapitulation. This journal discusses the outline of the academic application design lecture at Adi Husada Nursing Academy Surabaya.